EFFECTIVENESS OF THE ROLE OF INFORMATION SYSTEMS AND POLICY SYSTEMS IN EDUCATIONAL MANAGEMENT TO IMPROVE THE QUALITY OF PUBLIC SERVICE IN CILEUNYI DISTRICT, BANDUNG REGENCY - Ade Tutty R. Rosa (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
The background of this study includes the still low role of management information systems in improving the quality of public services and education service policies, especially in Cileunyi District, Bandung Regency. The aim is to find out the inhibiting factors, support in improving the quality of public services, education policy services. Qualitative descriptive research method, aims to provide a general description, an explanation of the variables studied in accordance with the focus of research includes the effectiveness of the role of information systems in managing information, producing information, presenting information and inhibiting factors, supporting in improving the quality of public services, education policy services . Using purposive sampling technique, accidental sampling, data collection techniques through in-depth interviews, research documents. The results of the study concluded that management information systems are very instrumental in managing information, producing information, presenting information. Using computer systems and information technology devices can be managed, sent to those who need them quickly, accurately, facilitating the completion of work tasks. Supporters in improving the quality of services including information and communication technology. This finding has maximally improved service to the public, services in determining policies in Education.